Lessons learned from the global recession - redesigned framework of key macroeconomic policies. (18th June 2019) - Trenovski, Borce; Tashevska, Biljana
This research provides a critical analysis of the available relevant theoretical and empirical literature regarding the key lessons about fiscal and monetary policy during the latest global crisis. The main contribution of this paper lies in offering a new redesigned framework for the key macroeconomic policies which can serve as a general guide to policymakers for designing these policies to respond to future financial and economic crises. Our critical analysis points out 14 lessons for monetary policy which the monetary authorities should take into account in the process of designing their future policies. The analysis also includes 14 lessons as a guide for governments to design their fiscal policy during future global imbalances, addressing the efficiency of fiscal policies during large-scale economic crises, the role and significance of fiscal space, the effectiveness of austerity programs, the coordination of fiscal policies on a global level, the coordination and mutual interactions with monetary policy, etc.